SAVINGS MOBILIZATION ON POVERTY ALLEVIATION AMONG PERI-URBAN HOUSEHOLDS IN KWALI AND BWARI AREA COUNCILS F.C.T ABUJA, NIGERIA - Juliana Ojochide Olori; Ogechi Cordelia Nwahia; FranÒ«ois SiÄ—wÄ— (Agricultural Socio-Economics Journal, 2021)
Savings is increasingly being acknowledged as a powerful tool for poverty alleviation but the peri- -urban households who are mostly, low cadre workers, peasant farmers and small-scale business owners lacks savings services. This study analyzed savings mobilization on poverty alleviation among peri-urban households in Kwali and Bwari Area Councils Abuja. Cross-sectional primary data was used in this study. The data was collected with the aid of a well-structured questionnaire administered to 185 peri-urban farming households. Descriptive statistics (mean, frequency and percentage), Foster Greer Thorbecke index and ordered logit regression were used to analyze the collected data. The results that emanated from the analysis reveals that 98% of respondents are within the economic active age while 82% of them had formal education and average household size of 4 person. About 93% of households saved in one form or the other. About 51% of the respondent are non-poor while 49% are poor based on analysis of poverty status which revealed poverty incidence of 49%, poverty depth of 28% and poverty severity of 56%. The results further reveals that primary occupation and education reduces the likelihood of not being poor, but there is an increment in the likelihood of being very poor while farm size, savings, access to credit andÂ  income generated from secondary activities increases the probability of being non-poor, but Â reduces the probability of being very poor. Therefore, households should be encouraged by Governmental agencies to engage in secondary economic activities for multiple stream of income to improve on their poverty status. In addition, government should facilitate the establishment of Financial Institutions in the Peri- Urban areas to inculcate saving habit among the people